1994
DOI: 10.1021/bp00029a007
|View full text |Cite
|
Sign up to set email alerts
|

Reversed Micellar Extraction of Charged Fusion Proteins

Abstract: We have investigated the use of charged fusion tails with the enzyme glucoamylase in reversed micellar extraction. The addition of the charged tails increased the fraction of enzymatically active protein recovered at a given pH, with the tails containing the largest number of charges being recovered at the highest level. The series of mutations also allows for investigation of the charge-dependent behavior of reversed micellar extraction. However, in this case, the change in protein charge via fusions had a le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…1. In a number of recent publications, extraction of proteins (both forward and backward) has been demonstrated using various reverse micellar systems [10][11][12][13][14][15][16][17][18]. These studies revealed that the extraction process is often controlled by various factors such as concentration and type of the surfactant, pH and ionic strength of the aqueous phase, concentration and type of the co-surfactants, salts, charge of the protein, temperature, water content, size and shape of reverse micelle, etc.…”
Section: Extraction and Back Extraction Processesmentioning
confidence: 99%
“…1. In a number of recent publications, extraction of proteins (both forward and backward) has been demonstrated using various reverse micellar systems [10][11][12][13][14][15][16][17][18]. These studies revealed that the extraction process is often controlled by various factors such as concentration and type of the surfactant, pH and ionic strength of the aqueous phase, concentration and type of the co-surfactants, salts, charge of the protein, temperature, water content, size and shape of reverse micelle, etc.…”
Section: Extraction and Back Extraction Processesmentioning
confidence: 99%
“…Reverse(d) micellar systems (RMS), isotropic solutions of water in oil (microemulsion) stabilized by surfactants, are powerful models that have found applications in biological compartmentalization studies, enzymatic catalysis, and separation of biomolecules. Among the surfactants that form reversed micelles (RM), the best known are the systems derived from AOT, which has a wedge-shaped molecular geometry that enables it to form stable RM without cosurfactants. The driving force for aggregate formation in apolar medium is attributable to the highly solvophobic sodium sulfosuccinate group of the AOT molecule.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, extensive work has been done in the field of application of RMS and the characterization of the systems has also been attempted. New techniques using small angle neutron scattering, photon correlation spectroscopy, and positron annihilation are proving to be useful in studying RMS. In most cases, the properties of the solubilized water pool have been the center of focus. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, an increase in the solubilization of the modified cytochromes in the AOT reversed micellar phase was observed. Forney et al took advantage of charged fusion proteins, which conferred high charge density on the protein surface, to improve the selectivity during protein separation process (Forney and Glatz, 1994, 1995). These charged fusion proteins consist of glucoamylase and the amino‐terminal fusions containing several additional asparatic acid residues (Asp, D).…”
Section: Introductionmentioning
confidence: 99%